An Update of Moisture Barrier Coating for Drug Delivery - Qingliang Yang; Feng Yuan; Lei Xu; Qinying Yan; Yan Yang; Danjun Wu; Fangyuan Guo; Gensheng Yang (MDPI AG, 2019)
Drug hydrolytic degradation, caused by atmospheric and inherent humidity, significantly reduces the therapeutic effect of pharmaceutical solid dosages. Moisture barrier film coating is one of the most appropriate and effective approaches to protect the active pharmaceutical ingredients (API) from hydrolytic degradation during the manufacturing process and storage. Coating formulation design and process control are the two most commonly used strategies to reduce water vapor permeability to achieve the moisture barrier function. The principles of formulation development include designing a coating formulation with non-hygroscopic/low water activity excipients, and formulating the film-forming polymers with the least amount of inherent moisture. The coating process involves spraying organic or aqueous coating solutions made of natural or synthetic polymers onto the surface of the dosage cores in a drum or a fluid bed coater. However, the aqueous coating process needs to be carefully controlled to prevent hydrolytic degradation of the drug due to the presence of water during the coating process. Recently, different strategies have been designed and developed to effectively decrease water vapor permeability and improve the moisture barrier function of the film. Those strategies include newly designed coating formulations containing polymers with optimized functionality of moisture barrier, and newly developed dry coating processes that eliminate the usage of organic solvent and water, and could potentially replace the current solvent and aqueous coatings. This review aims to summarize the recent advances and updates in moisture barrier coatings.